Microplastics in Aquatic Environments: A Systematic Review of Distribution and Biological Effects in Waters, Sediments, and Biota - Ayuni, Ni Putu Sri; Watiniasih, Ni Luh; Suyasa, I Wayan Budiarsa; Hendrawan, I Gede (Universitas Muhammadiyah Surakarta, 2025)
Currently, the issue of microplastic pollution in aquatic ecosystems is a significant cause for worry. Microplastics, which are tiny pieces of plastic, are readily absorbed by freshwater organisms, leading to detrimental impacts on their growth, reproduction, predatory abilities, and other aspects. This study aims to review the scientific literature on microplastics in freshwater environments including waters, sediments, and biota in order to identify their existence and impact. For such, a systematic review was conducted, following the PRISMA guidelines, applying a descriptive and statistical analysis to the data. The original research articles in